Escola cidadã integral técnica: atores, sujeitos, influências e a atuação da política em uma escola localizada no brejo paraibano - Silva, Thamyres Ribeiro da (2021)
The general objective of the research is to understand how the policy of full education's and full-time education's in a Technical Integral Citizen School (TICS) of Paraiba/Brazil has acted, considering the neoliberal categories that are introduced from the public-private partnership. This research, linked to the line of Educational Policies of the Master’s in Education of the Federal University of Paraíba, finds justification by to study a program that operates in more than 100 schools in the state, significantly altering aspects such as management, curriculum, and organizational culture of educational institutions, with direct and indirect participation of the private sector. From an analysis of documents dealing of the theme of Integral Education, it highlights the historical, political, and social aspects of each period, discussing the reform of High School and how this change underpinned the model of Integral Education in Paraíba, also pointing out the specific changes into the TICS, since they are directed to Integral Education and to Technical Education. Thus, it presents a qualitative approach, of descriptive kind in relation to the objectives outlined and makes use of the method of analysis of the Policy Cycle of Stephen Ball and Richard Bowe. Through the contextual dimensions of the politics of Stephen Ball, Meg Maguire, and Annette Braun as by voices of the subjects interviewed it was possible to understand how politics is being interpreted and acted into the institution, considering that teachers, students, and managers are denying and modifying ideas such as protagonist, evaluations, knowledge areas and relationships of coexistence, changed by the lack of infrastructure and others demands that are presented.